PENGARUH KARAKTERISTIK INDIVIDU TERHADAP DISTRES PADA PERAWAT DI RS X TEMBILAHAN - Yussy Rha, Warda; Faradisha, Jihan (Jurnal Kesehatan Lentera 'Aisyiyah, 2024)
Workplace stress can be described as the result of physical and emotional responses that occur when the demands of the job and the individual's ability to meet those demands differ. One profession at risk of experiencing workplace stress is nursing. Stress is divided into two types: eustress and distress. Distress in nurses can be caused by various factors, one of which is individual characteristics (such as gender, age, employment status, and length of service). Distress can lead to illness, absenteeism, and reduced work performance. Therefore, serious attention is needed from both workers and organizations. The purpose of this study is to determine the influence of individual characteristics on distress among nurses in the treatment room at X Hospital Tembilahan. This study uses a cross-sectional design conducted from May to August 2022. The population in this study consists of all nurses working in the treatment room at X Hospital Tembilahan. Distress was measured using the COPSOQ III questionnaire and the NIOSH Generic Job Stress questionnaire. Data were analyzed using Chi-square. The results of the statistical test for the gender variable showed a p-value of 0.031, indicating a significant effect of gender on the level of distress. The conclusion of the study, it was found that gender has an influence on the level of distress.